Covalent and Non-covalent Intermediates of an NAD Utilizing Enzyme - Human CD38 - Liu, Qun (2008)
Enzymatic utilization of nicotinamide adenine dinucleotide (NAD) has increasingly been shown to have fundamental roles in gene regulation, signal transduction, and protein modification. Many of the processes require the cleavage of the nicotinamide moiety from the substrate and the formation of a reactive intermediate. Using X-ray crystallography we show that human CD38, an NAD utilizing enzyme, is capable of catalyzing the cleavage reactions through both covalent and non-covalent intermediates, depending on the substrate used. The covalent intermediate is resistant to further attack by nucleophiles, resulting in mechanism-based enzyme inactivation. The non-covalent intermediate is stabilized mainly through H-bond interactions, but appears to remain reactive. Our structural results favor the proposal of a non-covalent intermediate during normal enzymatic utilization of NAD by human CD38 and provide structural insights into the design of covalent and non-covalent inhibitors targeting NAD utilization pathways.